The influence of language barriers on financial services: their contribution to financial access, client perceptions and attitudes towards traditional banking services. - Tigere, Patience (The IIE, 2023)
To support and permit financial inclusion of their citizens, developing nations must constantly fight to close the gap between the affluent and the poor. Studies have indicated that language barriers, inadequate education, illiteracy, and other resource constraints all play a part in this disparity. The purpose of the study was to investigate the influence that language barriers have on the ability of ordinary South Africans, particularly those from the lower income brackets, to access traditional financial services and the consequent consumer behaviour. When it was possible and for obvious reasons, more emphasis was placed on referencing developing countries throughout the African Continent rather than Western countries to fairly analyse previous literature and research. Based on the review of the literature available and the applicable theory, the researcher took on an interpretivist stance to approach the study where convenience sampling was used to recruit its participants. Semi-structured interviews were used as a research tool to gather data that was used to interrogate the researcher’s claim and to answer the research questions. Through these semistructured interviews, participants shared their personal experiences interacting with various financial service providers and how language barriers influenced their attitudes and perceptions of traditional banking services. Participants’ negative experience was one of the key findings which emerged in the discussions. A thematic analysis of these interviews gave insight into key themes which will serve to inform customer relationship policies, marketing and communication within the banking sector.
Keywords: Consumer behaviour; Income; Brand behaviour